Credibility of Genetic Algorithm (GA) for Power Efficient Routing and Reactive Protocols in MANET - Aggarwal, Juhi; Shelly, Shelly (International Journal of Computer Sciences and Engineering, 2025)
Mobile ad hoc networks (MANETs) does not depend upon the access points or it is an infrastructure less network that connects multiple nodes. The structure of the mobile network may alter frequently and in expected way. In mobile ad-hoc network (MANET), due to mobility of nodes. Energy consumption of nodes is important problem in MANET. In such scenario, link breaks in mobile network, when the battery power of a node is depleted and it results to stops services. Efficient shortest distance paths from source node to destination node is another a critical design issue in mobile ad hoc networks. Genetic Algorithm (GAs) gives the best possible solution to such kind of problems. Genetic algorithm has been used successfully in different applications. Genetic Algorithm will be helpful to minimize the route multiple times when any failure happens during transmission.This paper is giving the brief survey of genetic algorithm in mobile ad-hoc network